Distress Tolerance: Associations With Posttraumatic Stress Disorder Symptoms Among Trauma-Exposed, Cocaine-Dependent Adults. (January 2016) - Vujanovic, Anka A.; Rathnayaka, Nuvan; Amador, Christina D.; Schmitz, Joy M.
The present investigation examined associations between distress tolerance and posttraumatic stress disorder (PTSD) symptoms in a cocaine-dependent sample. Participants were comprised of 138 cocaine-dependent adults ( M age = 45.4, SD = 9.9; 81% male; 76.3% African American) who endorsed trauma exposure, defined according to Diagnostic and Statistical Manual of Mental Disorders (4th ed., text rev.; DSM-IV-TR ) PTSD Criterion A. Participants were administered interview-based measures and completed a series of self-report questionnaires. Results indicated that distress tolerance was significantly, incrementally (negatively) associated with PTSD symptom severity, contributing 6.8% of unique variance to the model ( p < .001); notably, the overall model explained 44.8% of variance in PTSD symptomatology. Distress tolerance also contributed between 2.7% and 6.8% of unique variance across each of the PTSD symptom clusters ( p s < .05). Incremental effects were documented, after accounting for the variance explained by theoretically relevant covariates (i.e., gender, cocaine-use severity, depressive symptoms, trauma-exposure severity). Theoretical and clinical implications are discussed.